An exploration into the relationships people with dementia have with physical objects: An ethnographic study. (November 2013) - Stephens, Alex; Cheston, Richard; Gleeson, Kate
In recent years there has been increasing interest in how different aspects of object relations theory might apply to dementia. While attachment theory in dementia has been well studied, there have been no systematic investigations of the way in which transitional objects are used by people with dementia. This study explores the relationship people with dementia have with physical objects using a focussed ethnographic method. Twenty-one residents and the staff of a care home for people with dementia were observed over a two-month period. Observations were recorded and analysed in light of Winnicott's criteria for transitional objects and incorporated the work of other key theorists. The ethnography found evidence that people with dementia have varied relationships with objects and can employ objects in a transitional way. The paper then explores the implications of this research for understanding the function of transitional objects for people with dementia. The findings suggest that that Winnicott's theory of transitional objects can provide a framework for understanding some of the processes of dementia.